2013
DOI: 10.1007/s11120-013-9890-6
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic potential of lithifying cyanobacteria-dominated thrombolitic mats

Abstract: Thrombolites are unlaminated carbonate deposits formed by the metabolic activities of microbial mats and can serve as potential models for understanding the molecular mechanisms underlying the formation of lithifying communities. To assess the metabolic complexity of these ecosystems, high throughput DNA sequencing of a thrombolitic mat metagenome was coupled with phenotypic microarray analysis. Functional protein analysis of the thrombolite community metagenome delineated several of the major metabolic pathwa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
64
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(75 citation statements)
references
References 53 publications
10
64
0
Order By: Relevance
“…Members of Scytonema were also found in the thrombolite metagenome from Highborne Cay, Bahamas (Mobberley et al 2013). Statistical analyses of the two microbial-mat samples show that we recovered the majority of the microbial community in our sampling (Good's Coverage 98% or greater) and that the alpha diversity of the biscuit mat is twice that of the flat mat.…”
Section: Discussionmentioning
confidence: 60%
“…Members of Scytonema were also found in the thrombolite metagenome from Highborne Cay, Bahamas (Mobberley et al 2013). Statistical analyses of the two microbial-mat samples show that we recovered the majority of the microbial community in our sampling (Good's Coverage 98% or greater) and that the alpha diversity of the biscuit mat is twice that of the flat mat.…”
Section: Discussionmentioning
confidence: 60%
“…Some microbial mats can lead to the formation of microbially induced mineral precipitations known as microbialites (Schneider et al, 2013), although the process of microbialite formation is still not completely understood . Microbialites can be delineated by their carbonate macrostructure, those with a laminated formation are often referred to as stromatolites, while their non-laminated clotted counterparts are referred to as thrombolites (Mobberley et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…A range of virulence genes were also identified that are often necessary to facilitate symbiotic relationships, and thus may provide clues to interactions between microorganisms in these systems. Metagenomic data on Bahaman stromatolites have been enlightening (Desnues et al, 2008;Khodadad and Foster, 2012;Mobberley et al, 2013), revealing a basis of a core microbial community structure (dominated by Cyanobacteria) and photosynthetic-induced carbonate precipitation. Recent in-depth studies have also combined metagenomic, stable isotopic and lipid analyses to study modern microbialites in Mexico (Breitbart et al, 2009;Nitti et al, 2012), indicating these metagenomes are capable of extensive environmental adaptation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The podcast specifically compared the functional gene diversity of microbes associated with two types of microbialites, laminated stromatolites an unlaminated thrombolites. The research included in the podcast was derived from two recently published studies on the functional gene complexity associated with these lithifying communities (Khodadad and Foster, 2012;Mobberley et al, 2013). The podcast contained various data slides, graphs, and interpretations of the two types of microbialite communities.…”
Section: Scientific Inquiry Exercise Structurementioning
confidence: 99%